(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
We are excited to announce a PLAIO-sponsored webinar that will celebrate and further the major themes and questions of the 5th VPL Biennale, “People, Validation and Power: Democracy in Action?” upon which this special issue of PLAIO is based. Please expect more details about this opportunity to further our community conversation. We hope you will be able to join us.